Polarisation as a challenge to parliamentary governance - Carroll, Royce; Bäck, Hanna ; 0000-0002-0296-9419 (Democracy at the Crossroads – Challenges for Governance and Representation : Essays in Honour of Thomas Saalfeld, 2026)
This chapter examines elite polarisation as a challenge to governance in parliamentary democracies. We emphasise the distinction between ideological polarisation based on substantive policy disagreements from affective polarisation, characterised by identity-based animosity that creates barriers to cooperation even when policy compromise might otherwise be possible. While parliamentary regimes have mechanisms to resolve ideological conflicts, affective polarisation poses distinct challenges to government formation, policymaking, and cabinet stability. We highlight that parliamentary systems possess institutional “shock absorbers” that can mitigate the effects of elite polarisation but that these may vary in effect depending on whether conflicts between elites are based on policy disagreement or identity. We conclude with a discussion of the broader consequences of affective polarisation for democracy. By distinguishing between ideological and affective aspects of elite conflict, we can improve our understanding of contemporary challenges to parliamentary democracy where elite polarisation is of increasing importance.